Live-animal measurements and carcass characteristics of Sudan Desert and Australian Merino sheep - Babiker, S.A.; Mohamed, S.A. (1990)
Sudan Desert sheep and Australian Merino sheep were compared for live-animal measurements, carcass conformation and composition. The Desert sheep had significantly longer trunks (p